Modulation of Self‐Assembly Enhances the Catalytic Activity of Iron Porphyrin for CO2 Reduction. Issue 22 (9th March 2021) - Tasaki, Masahiro; Okabe, Yuki; Iwami, Hikaru; Akatsuka, Chiharu; Kosugi, Kento; Negita, Kohei; Kusaka, Sinpei; Matsuda, Ryotaro; Kondo, Mio; Masaoka, Shigeyuki
Abstract: Electrochemical reduction of CO2 in aqueous media is an important reaction to produce value‐added carbon products in an environmentally and economically friendly manner. Various molecule‐based catalytic systems for the reaction have been reported thus far. The key features of state‐of‐the‐art catalytic systems in this field can be summarized as follows: 1) an iron‐porphyrin‐based scaffold as a catalytic center, 2) a dinuclear active center for the efficient activation of a CO2 molecule, and 3) a hydrophobic channel for the accumulation of CO2 . This article reports a novel approach to construct a catalytic system for CO2 reduction with the aforementioned three key substructures. The self‐assembly of a newly designed iron‐porphyrin complex bearing bulky substituents with noncovalent interaction ability forms a highly ordered crystalline solid with adjacent catalytically active sites and hydrophobic pores. The obtained crystalline solid serves as an electrocatalyst for CO2 reduction in aqueous media. Note that a relevant iron‐porphyrin complex without bulky substituents cannot form a porous structure with adjacent active sites, and the catalytic performance of the crystals of this relevant iron‐porphyrin complex is substantially lower than that of the newly developed catalytic system. The present study provides a novel strategy for constructing porous crystalline solids for small‐molecule conversions. Abstract : The self‐assembly of iron‐porphyrin complexes bearing bulky substituents with intermolecular interaction ability ("space modulators") affords crystalline solids with adjacent catalytically active sites and hydrophobic pores. The crystalline solid can catalyze the CO2 reduction reaction to produce CO under electrochemical conditions in aqueous media. The present study provides a novel approach to construct porous crystalline solids for small‐molecule conversions.